Does caffeine ingestion affect the lower-body post-activation performance enhancement in female volleyball players? - Filip-Stachnik, A.; Spieszny, M.; Stanisz, L.; Krzysztofik, M. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Post-activation performance enhancement (PAPE) is a physiological phenomenon that acutely improves voluntary muscular performance following a conditioning activity. A large and growing body of literature has investigated different strategies to induce a PAPE stimulus; however, little attention has been given to whether acute caffeine ingestion could augment the effect of PAPE on subsequent performance. This study evaluated the acute effects of caffeine ingestion and back squat conditioning activity on subsequent countermovement jump (CMJ) performance in female semi-professional volleyball players.